PENGARUH MOTIVASI EKSTRINSIK, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. SURYA BRATASENA PLANTATION DI PELALAWAN - Ismilanto '; Machasin '; Rendra Wasnury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine how the Effects of Extrinsic Motivation, Discipline of Work and Work Environment on Employee Productivity at PT. Bratasena Plantation. In this study the authors use independent variables is extrinsic motivation (X1), work discipline (X2) and work environment (X3), as the dependent variable productivity (Y). Slovin technique is used to obtain the sample population. To analyze our data, we used multiple regression analysis. testing while t-test, f-test and coefficient of determination (R2) is used to test our hypothesis. From the research that has been done with multiple linear regression analysis with the help of IBM SPSS version 21, it can be concluded that extrinsic motivation, work discipline and work environment positive and significant impact on work productivity with the formula Y = -0.246 + 0.733 (X1) + 0.169 (X2) + 0.104 (X3) and the contribution of Fwhich amounted to 67.825 against the dependent variable and the significant level of 0.000Keywords : Extrinsic Motivation, Work Discipline, Work Environment and Work Productivity